1996
DOI: 10.1039/cc9960000725
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic conversion of polyethylene into fuels over mesoporous MCM-41

Abstract: Tetrahedral Al-containing MCM-41, prepared under ambient conditions, exhibits suitable catalytic properties for the conversion of low-density polyethylene into hydrocarbon feedstocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 4 publications
1
73
1
Order By: Relevance
“…6. This enhancement is also seen in the nanocomposites; for instance, long spacing rises from 39.7 to 46.1 nm in HDPE/MCM-41 (14).…”
Section: Morphological and Structural Characterisationmentioning
confidence: 69%
See 3 more Smart Citations
“…6. This enhancement is also seen in the nanocomposites; for instance, long spacing rises from 39.7 to 46.1 nm in HDPE/MCM-41 (14).…”
Section: Morphological and Structural Characterisationmentioning
confidence: 69%
“…While the catalytic effect of the inorganic material in the decomposition of polymers was also observed with several zeolites [16,28,29], MCM-41 materials appear to be more active in this process, probably due to their larger pore diameters [30]. These results suggest that the recycling of the nanocomposites at the end of their lifetime service, by reutilisation in chemical processes or in the production of liquid fuels, would be more favourable [14,31]. Fig.…”
Section: Thermal Characterisationmentioning
confidence: 70%
See 2 more Smart Citations
“…A similar effect has been found by Marcilla 42 et al when studying the degradation of PE under N 2 , in the presence and absence of mesoporous MCM-41, by thermogravimetric analysis (TGA). Aguado 43 et al have also shown the efficiency of mesoporous aluminosilicate MCM-41 as promoter towards degradation of polyolefins into liquid fuels. Nowadays, this might be quite interesting in relation to the degradation of these polyolefins into basic petrochemicals as feedstock or fuel for downstream processes after their life service, making these self-reinforced polyolefinic materials environmentally welcome and with an added value.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%